Chlamydia pneumoniae infection induced allergic airway sensitization is controlled by regulatory T-cells and plasmacytoid dendritic cells. - Timothy R Crother; Nicolas W J Schröder; Justin Karlin; Shuang Chen; Kenichi Shimada; Anatoly Slepenkin; Randa Alsabeh; Ellena Peterson; Moshe Arditi (PLoS ONE)
Chlamydia pneumoniae (CP) is associated with induction and exacerbation of asthma. CP infection can induce allergic airway sensitization in mice in a dose- and time-dependent manner. Allergen exposure 5 days after a low dose (mild-moderate), but not a high dose (severe) CP infection induces antigen sensitization in mice. Innate immune signals play a critical role in controlling CP infection induced allergic airway sensitization, however these mechanisms have not been fully elucidated. Wild-type, TLR2-/-, and TLR4-/- mice were infected intranasally (i.n.) with a low dose of CP, followed by i.n. exposure to human serum albumin (HSA) and challenged with HSA 2 weeks later. Airway inflammation, immunoglobulins, eosinophils, and goblet cells were measured. Low dose CP infection induced allergic sensitization in TLR2-/- mice, but not in TLR4-/- mice, due to differential Treg responses in these genotypes. TLR2-/- mice had reduced numbers of Tregs in the lung during CP infection while TLR4-/- mice had increased numbers. High dose CP infection resulted in an increase in Tregs and pDCs in lungs, which prevented antigen sensitization in WT mice. Depletion of Tregs or pDCs resulted in allergic airway sensitization. We conclude that Tregs and pDCs are critical determinants regulating CP infection-induced allergic sensitization. Furthermore, TLR2 and TLR4 signaling during CP infection may play a regulatory role through the modulation of Tregs.